1989
DOI: 10.2151/jmsj1965.67.4_541
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Carbon Dioxide Flux over the Ocean

Abstract: Atmospheric fluctuations of carbon dioxide, humidity and temperature were simultaneously measured over the ocean,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Apparently, the CO 2 density fluctuation showed the contrary behaviour from the CO 2 mixing ratio under the significant influence of air temperature and H 2 O density fluctuations. Thus, in the present study, the total CO 2 flux by the OPEC changed sign due to the WPL correction, which is similar to the results given by previous studies (Ohtaki et al, 1989;Kondo and Tsukamoto, 2007).…”
Section: Atmospheric Turbulent Fluctuationssupporting
confidence: 92%
“…Apparently, the CO 2 density fluctuation showed the contrary behaviour from the CO 2 mixing ratio under the significant influence of air temperature and H 2 O density fluctuations. Thus, in the present study, the total CO 2 flux by the OPEC changed sign due to the WPL correction, which is similar to the results given by previous studies (Ohtaki et al, 1989;Kondo and Tsukamoto, 2007).…”
Section: Atmospheric Turbulent Fluctuationssupporting
confidence: 92%
“…The general features of the fluxes derived by the three methods agreed well and the absolute values of those fluxes were positively correlated with U. Table 3 Ohtaki et al (1989) reported upward efflux at the same site as Iwata et al (2004) contributions dominated in estimating F C,EC and F C,VA and were positively correlated with U (Figs. 13b, c, e, and f ).…”
Section: Comparison Of Fluxes Derived By the Three Methodsmentioning
confidence: 61%
“…λE, and net gain G, in previous studies and in this study. Results from Kondo (1976) were obtained from his Table A1; results from Ohtaki et al (1989) were averaged from their Table 2; results from Ishii and Kondo (1993) were from their Figure 10c; results from and were from their …”
Section: Energy Budgets Over the Sea Surfacementioning
confidence: 99%
“…Practically, sensible and latent heat fluxes evaluated by the eddy covariance technique are used to calculate water vapor and CO2 fluxes by the mean vertical flow (Webb or WPL correction). Ohtaki et al (1989) suggested that the Webb CO2 flux due to air density fluctuation is larger than the raw CO2 flux and changes the transport direction of the total CO2 flux over the coastal sea surface. Kondo and Tsukamoto (2007) also confirmed these results over the open ocean surface.…”
Section: Introductionmentioning
confidence: 99%